Design and performance assessment of a single-storey unreinforced foam concrete shear wall building against earthquake and severe wind hazards - Santelices, Joanna Patricia B.; Suiza, Raniel M.; Hernandez, Jaime Y. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The Philippines is considered the fourth most disaster-prone country in the world, enduring numerous natural calamities such as typhoons and earthquakes annually. These disasters cause extensive damages, in terms of human casualties, socioeconomic impact, and destruction of infrastructure. A possible means of mitigating structural damage is by constructing buildings using foam concrete, a cement-based slurry with entrained foam in the plastic mortar. In this research, the severe wind and earthquake performance of a foam concrete house was assessed to determine what wind speed and earthquake intensity these houses will be able to withstand. Nonlinear static pushover analysis was used to assess the structure's performance against earthquakes. In the simulation, the structure began to experience slight damage under an intensity 9.4 earthquake, and total damage was achieved under an intensity 10.9 earthquake. Computational fluid dynamics was used to assess the performance of the structure against severe winds. The structure was subjected to increasing wind speeds from different directions, and corresponding damages were obtained. The analysis showed that the lowest wind speed at which the structure began to experience minor damage at 235 kph with wind coming from the 90° direction, and the lowest wind speed at which the structure reached a state of total damage was 295 kph under wind coming from the 0° direction
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Structural dynamics; Earthquake resistant design; Wind resistant design